In vivo biocompatibility of boron doped and nitrogen included conductive‐diamond for use in medical implants. (21st January 2015) - Garrett, David J.; Saunders, Alexia L.; McGowan, Ceara; Specks, Joscha; Ganesan, Kumaravelu; Meffin, Hamish; Williams, Richard A.; Nayagam, David A.X.
Abstract: Recently, there has been interest in investigating diamond as a material for use in biomedical implants. Diamond can be rendered electrically conducting by doping with boron or nitrogen. This has led to inclusion of boron doped and nitrogen included diamond elements as electrodes and/or feedthroughs for medical implants. As these conductive device elements are not encapsulated, there is a need to establish their clinical safety for use in implants. This article compares the biocompatibility of electrically conducting boron doped diamond (BDD) and nitrogen included diamond films and electrically insulating poly crystalline diamond films against a silicone negative control and a BDD sample treated with stannous octoate as a positive control. Samples were surgically implanted into the back muscle of a guinea pig for a period of 4–15 weeks, excised and the implant site sectioned and submitted for histological analysis. All forms of diamond exhibited a similar or lower thickness of fibrotic tissue encapsulating compared to the silicone negative control samples. All forms of diamond exhibited similar or lower levels of acute, chronic inflammatory, and foreign body responses compared to the silicone negative control indicating that the materials are well tolerated in vivo . © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 19–26, 2016.